Enterococcus faecalis α1–2‐mannosidase (EfMan‐I): an efficient catalyst for glycoprotein N‐glycan modification. Issue 3 (8th October 2019) - Li, Yanhong; Li, Riyao; Yu, Hai; Sheng, Xue; Wang, Jing; Fisher, Andrew J.; Chen, Xi
Abstract : While multiple α 1–2‐mannosidases are necessary for glycoprotein N‐glycan maturation in vertebrates, a single bacterial α1–2‐mannosidase can be sufficient to cleave all α1–2‐linked mannose residues in host glycoprotein N‐glycans. We report here the characterization and crystal structure of a new α1–2‐mannosidase (EfMan‐I) from Enterococcus faecalis, a Gram‐positive opportunistic human pathogen. EfMan‐I catalyzes the cleavage of α1–2‐mannose from not only oligomannoses but also high‐mannose‐type N‐glycans on glycoproteins. Its 2.15 Å resolution crystal structure reveals a two‐domain enzyme fold similar to other CAZy GH92 mannosidases. An unexpected potassium ion was observed bridging two domains near the active site. These findings support EfMan‐I as an effective catalyst for in vitro N‐glycan modification of glycoproteins with high‐mannose‐type N‐glycans. Abstract : EfMan‐I from Enterococcus faecalis (crystal structure shown on the left) efficiently catalyzing the cleavage of all α1–2‐linked mannose residues in high‐mannose N‐glycans on glycoproteins.